CEBPA-associated familial acute myeloid leukemia mimicking Werner syndrome: a case report - Demaret, Tanguy; Feret, Damien; Lambert, Barbara; Pranger, Delphine; Dargent, Jean-Louis; Martin Martinez, Maria Dolores; Renda, Antonio; Maystadt, Isabelle (Frontiers in Genetics, 2025)
CEBPA-associated familial acute myeloid leukemia (AML) is an autosomal dominant leukemia predisposition syndrome associated with germline variants in the CEBPA gene. Werner syndrome (WS) is an autosomal recessive progeroid syndrome causing premature aging and malignancies (e.g., AML). We report a 41-year-old man referred for medical genetic evaluation because of 3 synchronous tumors (colon, kidney, and thyroid) and premature aging. He underwent hematopoietic stem cell transplantation (HSCT) at 12 years of age because of AML diagnosed 3 years earlier. His sister (donor for the HSCT) and his brother later developed AML, as did two of her sister’s three children. The patient met the clinical criteria for a “probable” WS, but duo-based (urine and blood DNA) whole exome sequencing did not confirm this diagnosis. A heterozygous c.350del p.(Gly117Alafs*43) pathogenic variant in the CEBPA gene was found in the proband’s urine and blood DNA, and in his affected relatives. We postulate that AML management led to adverse effects in the proband, mimicking a WS phenotype (phenocopy). To our knowledge, this is the first report of a leukemia predisposition syndrome mimicking a progeroid syndrome. The diagnosis allowed for personalized medicine (i.e., lifelong regular complete blood count check-up) in the proband and his affected relatives.